Islamic Counselling Model to Increase Religious Commitment (Study of Students at the University UIN Bandung) - Fenti Hikmawati (UIN Sunan Gunung Djati Bandung, 2013)
The study aims to test the effectiveness of Islamic counseling model for helping the students to tight their religious commitment. The religious commitment is covered in three major Islamic teachings: Iman (faith), Islam (surrender to Allah), and lhsan (state of being observed by Allah). The model of Islamic counseling aims to tight students' religious commitment must to be applied immediately because the preface study reveals some students' religious commitment were not strong enough, their behavior and thinking symptoms tend to not appropriate yet with Islam norm among their association and conception toward the truth of God. To achieve the aim, the study was carried out with three steps: (1) designing a model of counseling; (2) trying out field study, using pretest-post test control group experimental design with 140 students of Islamic Religion Education, the Faculty of Tarbiyah and Teaching, State Islamic University, Sunan Gunung Djati, Bandung. Of 140 students, 70 students are from the classes: A (32 people), B (38 people), involved in control group and the test; 37 people from class C, and 33 students from class D involved in the experiment group, and; (3) designing a final model by revising the model tried-out. The variable involved three major Islamic dimensions: the iman, Islam, and ihsan of the students. The model was designed based on the theory put forward by Musfir bin Said Az-Zalmmi, that is, an integrated counseling model. The model combines and employs the ideas from other concepts into a tightly united concept, called Islamic concept. Upon completing analysis, it was found that the new concept is significantly effective to enhance students' religious commitment. A Model of Islamic Counseling (MIC) is an alternative-counseling model that can be employed for teenagers/ students to enhance their religious commitment. The study recommends that: (1) MIC can be applied to fifth semester students in the Faculty of Tarbiyah State Islamic University; (2) the application of MIC collaborates with professional and proportional elements relevant to the expected aim; (3) the researchers studying the same materials use the appropriate method appropriate to individual characteristics referring to Islamic norms kaffah (integrally).